Evaluation of Contribution and Distribution of Special Allocation Fund (DAK) Physical Assignment Thematic of Sustainable Economic Infrastructure Provision - Andi Setyo Pambudi; Devy Paramitha Agnelia; Desak Made Annisa Cahya Putri (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
Field implementation of the Special Allocation Fund (DAK) Assignment, especially the thematic of Sustainable Economic Infrastructure Provision in 2021 from the local government's point of view, is a significant matter because it is related to development priorities achievement, especially during the COVID-19. Concerning the need for information on the spatial distribution of the DAK allocation for Physical Assignment, especially the Thematic of Sustainable Economic Infrastructure Provision (PIEB) for the 2021 fiscal year, it is necessary to carry out a series of spatial analyzes showing the distribution of the DAK Physical allocation and its contribution to regional development using a budget comparison approach. Spatial analysis was carried out for mapping: 1) The contribution and role of the DAK Physical allocation to the local government budget in 2021; 2) Contribution of DAK Physical Assignment allocation of PIEB to the local government budget in 2021; 3) Contribution of DAK Physical Assignment allocation of PIEB (Small and Medium Industries (IKM), Roads, Tourism, and the Environment) to the local government budget in the fiscal year of 2021. In general, regions with a high category of DAK Physical contributions are dominated by provinces in the Eastern Region of Indonesia. On average, the DAK Physical Assignment allocation of Sustainable Economic Infrastructure Provision contributes 0.5% to the Provincial Budget. It is necessary to monitor and evaluate the implementation of DAK Physical for the Sustainable Economic Infrastructure Provision and improve coordination between institutions, both at the central and regional levels.